Efficacy and safety clinical trial with efavirenz in patients diagnosed with adult Niemann-pick type C with cognitive impairment. Issue 48 (2nd December 2022) - Gascón-Bayarri, Jordi; Simon, Petru Cristian; Llop, Roser; Carnaval, Thiago; Ledesma, María Dolores; Rico, Imma; Sánchez-Castañeda, Cristina; Campdelacreu-Fumadó, Jaume; Calvo-Malvar, Nahum; Cos, Mònica; de Lama, Eugenia; Cortés-Romera, Montserrat; et al.
Abstract : Background: Niemann-Pick disease Type C (NPC) is a genetic, incurable, neurodegenerative disorder. This orphan disease is most frequently caused by mutations in the NPC1 protein, resulting in intralysossomal cholesterol accumulation. NPC1 is found in neuronal cell bodies, axon terminals and synaptosomes, suggesting it plays a role in lysosomal degradation pathway and in synaptic transmission. Neuronal function is especially vulnerable to NPC1 deficiency and synaptic changes seem a key element in disease development. Currently, Miglustat (Zavesca®) is the only approved treatment for NPC. However, preclinical evidence showed that low-dose Efavirenz reverted synaptic defects through pharmacological activation of the enzyme CYP46. Methods: This is a single-center, phase II clinical trial to evaluate the efficacy and safety of Efavirenz in addition to standard of care in patients diagnosed with adult or late juvenile-onset NPC with cognitive impairment. All enrolled patients will be treated orally with 25 mg/d of Efavirenz for 52 weeks (1 year). Secondary objectives include evaluating clinical (neurological and neuropsychological questionnaires) and biological (imaging and biochemical biomarkers) parameters. Discussion: NPC is still an unmet medical need. Although different therapeutic approaches are under study, this is the first clinical trial (to the best of our knowledge) studying the effects of Efavirenz in adult- and late-juvenile-onset NPC. Despite the small sample size and the single-arm design, we expect the results to show Efavirenz's capacity of activating the CYP46 enzyme to compensate for NPC1 deficiency and correct synaptic changes, therefore compensating cognitive and psychiatric changes in these patients. This study may provide direct benefit to enrolled patients in terms of slowing down the disease progression.